Two-dimensional soft nanomaterials: A fascinating world of materials - Zhuang, Xiaodong; Mai, Yiyong; Wu, Dongqing; Zhang, Fan; Feng, Xinliang (Advanced Materials, 2015)
The discovery of graphene has triggered great interest in two-dimensional (2D) nanomaterials for scientists in chemistry, physics, materials science, and related areas. In the family of newly developed 2D nanostructured materials, 2D soft nanomaterials, including graphene, BxCyNz nanosheets, 2D polymers, covalent organic frameworks (COFs), and 2D supramolecular organic nanostructures, possess great advantages in light-weight, structural control and flexibility, diversity of fabrication approaches, and so on. These merits offer 2D soft nanomaterials a wide range of potential applications, such as in optoelectronics, membranes, energy storage and conversion, catalysis, sensing, biotechnology, etc. This review article provides an overview of the development of 2D soft nanomaterials, with special highlights on the basic concepts, molecular design principles, and primary synthesis approaches in the context.
CRIS-Team Scopus Importer:2023-03-20